Efektivitas Token Economy Terhadap Perawatan Diri Pada Klien Skizofrenia - Helmi Wardini; Nofrida Saswati; Isti Harkomah (Lontara Journal of Health Science and Technology, 2024)
Schizophrenia with symptoms of self-care deficit which is the second most common symptom in Jambi Provincial Hospital. Self-care deficit is a disorder of the ability to carry out self-care activities, therefore it is necessary to provide program methods, one of which is the token economy method. To determine the effectiveness of the token economy for self-care in schizophrenic clients. This research is a pre-experimental study with a one-group pre-test and post-test design. The population in this study were all schizophrenic clients with self-care deficit problems who were treated in the quiet room of the Jambi Provincial Mental Hospital for the period October 2022. In this study, samples were taken using a total sampling technique of 21 people. The instrument uses observation sheets and analyzes using univariate and bivariate with the T-Test test. There is the effectiveness of the token economy for self-care of schizophrenic clients at the Jambi Province Mental Hospital in 2022 with a p-value of 0.000. The token economy is effective for self-care in schizophrenic clients.